A Retrospective Analysis of Clinical and Laboratory Data of Patients with Factor VII Deficiency: A Single Centre Experience - Iwaniec, Teresa; Zdziarska, Joanna; Musiał, Jacek; Sanak, Marek (Hämostaseologie, 2019)
Bleeding phenotype in patients with congenital factor VII (FVII) deficiency is highly variable. No direct correlation between FVII activity and bleeding tendency is noted. The aim of this study was to analyse clinical and laboratory phenotype of patients with FVII deficiency treated in one haemophilia treatment centre in Little Poland. Clinical and laboratory data of 106 patients were collected retrospectively. Bleeding symptoms were evaluated according to the Bleeding Assessment Tool. The mean FVII activity was 19.5% (range: 1.0–49.2) and the mean prothrombin time (PT) was 29.7 seconds (range: 13.2–64.8), comparable in both sexes. Activity was lower than 1% in 6.6% of individuals. The average age at diagnosis (31.2 years; range: 1–76) did not correlate with FVII activity. Half of the patients were diagnosed incidentally, mostly due to routine PT measurement. The most frequently reported symptoms were gum, nose and tooth extraction bleeds. A total of 22.6% of patients remained asymptomatic and 60.4% never required replacement therapy. Thrombotic episodes were diagnosed in five women (4.7%). In conclusion, the clinical picture of the analysed group is similar to the previously described. It should be stressed that a significant risk of bleeds, including joint haemorrhages, can be expected in patients with mildest FVII deficiency (>26%) as well. The rate of thrombosis (4.7%) was similar to other reports, with all affected patients having strong prothrombotic risk factors or being intensively treated with FVII concentrate.
Keywords: congenital FVII deficiency; bleeding symptoms; diagnosis; replacement therapy; thrombosis